Phase stability of the amorphous phase and non-equilibrium phase in a β Ti-Zr-based shape memory alloy. (1st April 2021) - Li, Shuanglei; Choi, Mi-Seon; Nam, Tae-Hyun
Abstract: This work presents the amorphization of metastable β phase and the phase stability of the amorphous phase and non-equilibrium phase in a Ti-Zr-Nb-Sn shape memory alloy (SMA). The amorphous phases with lenticular shape uniformly embedded in β matrix are observed in the twin-jet-electropolished thin foil specimen for transmission electron microscope (TEM) observations. Meanwhile, a co-existence of non-equilibrium athermal ω phase and nanodomain phases are found to be formed in the β matrix. These non-equilibrium phases could favorably compete with the amorphous phase formation and render the amorphous phases are not formed, leading to that the amorphous phase is not observed in the bulk specimens for X-ray diffraction (XRD) and electron back-scattered diffraction (EBSD) and also TEM specimen prepared by a focused ion beam (FIB). The formation of the amorphous phase in the twin-jet-electropolished TEM specimen is thought to be due to the hydrogen-related artifacts introduced during twin-jet electropolishing. Graphical abstract: Image, graphical abstract